Effects of pre- and post-emergence weed control on weed population and maize yield in different tillage systems - M. Knežević; M. Đurkić; I. Knežević; Z. Lončarić (Plant, Soil and Environment, 2003)
The effect of chemical weed control with reduced herbicide rates (pre-em., pre-em. + post-em., post-em.) on weed population density and maize yield was compared in three tillage systems (mouldboard, chisel, disk harrowing) for lessive pseudogleyic soil in north-eastern Croatia(1997-1999). These main weeds were present in all tillage variants: Echinochloa crus-galli (L.) PB., Chenopodium album L., Ambrosia artemisiifolia L., Polygonum lapathifolium L., Equisetum arvense L. and Calystegia sepium (L.) R.Br. The density of all weeds was significantly affected by tillage and it ranged from 204 plants on untreated plots with mouldboard to 372 and 421 plants per m2 with chisel ploughing and disk harrowing, respectively. In comparison with standard tank-mixture of atrazine herbicide (metolachlor 50% & atrazine 20%) at the recommended rate, atrazine-free herbicide combinations (metolachlor + 50% prosulfuron & 30% primisulfuron-methyl; sulcotrione + bromoxynil; thifensulfuron-methyl + nicosulfuron) showed a similar total efficacy of weed control (95-96%). Band spraying with standard treatment at a half-recommended rate combined with mechanical weed control brought a satisfactory total weed reduction (83-87%). The weed control methods had no effects on maize yields that were significantly affected by year and tillage. Compared to the highest yield with mouldboard ploughing (10.2 t/ha), average percent yield depressions with chisel ploughing and disk harrowing were 10 and 22%, respectively.